Pharmacological Silencing of MicroRNA-152 Prevents Pressure Overload–Induced Heart Failure. (March 2020) - LaRocca, Thomas J.; Seeger, Timon; Prado, Maricela; Perea-Gil, Isaac; Neofytou, Evgenios; Mecham, Brigham H.; Ameen, Mohamed; Chang, Alex Chia Yu; Pandey, Gaurav; Wu, Joseph C.; Karakikes, Ioannis
Abstract : Background: MicroRNAs are small, noncoding RNAs that play a key role in gene expression. Accumulating evidence suggests that aberrant microRNA expression contributes to the heart failure (HF) phenotype; however, the underlying molecular mechanisms are not well understood. A better understanding of the mechanisms of action of microRNAs could potentially lead to targeted therapies that could halt the progression or even reverse HF. Methods and Results: We found that microRNA-152 (miR-152) expression was upregulated in the failing human heart and experimental animal models of HF. Transgenic mice with cardiomyocyte-specific miR-152 overexpression developed systolic dysfunction (mean difference, −38.74% [95% CI, −45.73% to −31.74%]; P <0.001) and dilated cardiomyopathy. At the cellular level, miR-152 overexpression perturbed mitochondrial ultrastructure and dysregulated key genes involved in cardiomyocyte metabolism and inflammation. Mechanistically, we identified Glrx5 (glutaredoxin 5), a critical regulator of mitochondrial iron homeostasis and iron-sulfur cluster synthesis, as a direct miR-152 target. Finally, a proof-of-concept of the therapeutic efficacy of targeting miR-152 in vivo was obtained by utilizing a locked nucleic acid–based inhibitor of miR-152 (LNA 152) in a murine model of HF subjected to transverse aortic constriction. We demonstrated that animals treated with LNA–152 (n=10) showed preservation of systolic function when compared with locked nucleic acid–control treated animals (n=9; mean difference, 18.25% [95% CI, 25.10% to 11.39%]; P <0.001). Conclusions: The upregulation of miR-152 expression in the failing myocardium contributes to HF pathophysiology. Preclinical evidence suggests that miR-152 inhibition preserves cardiac function in a model of pressure overload–induced HF. These findings offer new insights into the pathophysiology of HF and point to miR-152-Glrx5 axis as a potential novel therapeutic target. Abstract : Supplemental Digital Content is available in the text.